1971
DOI: 10.1037/h0031563
|View full text |Cite
|
Sign up to set email alerts
|

Constancy in short-term memory: Bits and chunks.

Abstract: The question asked was, What are the constants (if any) of the short-term memory (STM) system? Information load (alphabet size), explicit coding instructions, and stimulus exposure time were varied in an STM task. Exposure time was found to be a critical factor in the operation of the memorial system. In general, STM was found to be constant for information at very short exposure times (less than 1 sec.) and constant for chunks at longer exposure intervals, although systematic discrepancies from memorial const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…On some readings, chunking requires conceptual recoding of the type involved when parsing PBSBBCCNN into PBS, BBC, and CNN. Such recoding entails that each of the newly created representational units corresponds to an existing, unitary concept in long-term memory (e.g., CNN is the media corporation that employs Wolf Blitzer) (36,37). A different definition of chunking also requires conceptual knowledge, but does not require recoding.…”
Section: Resultsmentioning
confidence: 99%
“…On some readings, chunking requires conceptual recoding of the type involved when parsing PBSBBCCNN into PBS, BBC, and CNN. Such recoding entails that each of the newly created representational units corresponds to an existing, unitary concept in long-term memory (e.g., CNN is the media corporation that employs Wolf Blitzer) (36,37). A different definition of chunking also requires conceptual knowledge, but does not require recoding.…”
Section: Resultsmentioning
confidence: 99%
“…Another promising strategy would be to begin with unconnected units and teach the subjects new chunks (with learning assessment), so that the chunks are known to the experimenter before they are used in a working memory task. Kleinberg and Kaufman (1971) carried out one procedure in which the role of chunking in recall was tackled rather directly. Subjects were presented with clusters of 13 dots, each forming a complex, symmetrical pattern.…”
Section: R221 a Strategy For Research To Identify Chunksmentioning
confidence: 99%
“…One of the factors that determines whether the benefit of chunking outweighs the cost may be the size of the chunks; the capacity savings achieved by using a larger chunk may outweigh the cost of encoding and decoding those chunks. Indeed, several studies have demonstrated that chunking really does have a cost (Glanzer & Fleishman, 1967;Huang & Awh, 2018;Kleinberg & Kaufman, 1971;Pollack & Johnson, 1965). Glanzer and Fleishman (1967) had participants recall sequences of nine binary digits presented simultaneously for 0.5s.…”
Section: The Cost Of Chunkingmentioning
confidence: 99%
“…WebPlotDigitizer https://automeris.io/WebPlotDigitizer/index.html) Kleinberg and Kaufman (1971) tested memory for visual patterns. At fast presentation rates (less than one second) memory was constant in terms of amount of information, but memory became constant in chunks at slower rates.…”
Section: The Cost Of Chunkingmentioning
confidence: 99%